IDENTIFIKASI KEBERADAAN JALUR GOA BAWAH TANAH (BUNKER) BERDASARKAN ANALISIS DATA MAGNETIK DI DESA JEMBAYAN - ., Suryadi; Supriyanto, Supriyanto; Djayus, Djayus (GEOSAINS KUTAI BASIN, 2021)
Existence of underground cave (bunker) in Jembayan has been known for long, but underground pathway was sealed and lost due to landslide. Goal of this research is to identify existence of underground cave (bunker) pathway based on magnetic data analysis. Topographic data acquisition with Theodolit and magnetic data acquisition with Geotron Model G5 Proton Memory Magnetometer at May 2nd 2019 with 98 observation point and space between observation point of 5 meters. Data processing carried out with diurnal variation corection, IGRF correction,. Upward continuation and reduce to pole. Modeling cared out by analyzing magnetic field anomaly that has been reduced to pole and upward continuation with 10 m height. Based on the analysis results and pathway cave magnetic data interpretation in Jembayan area shows existence of continuity from observation bunker and main bunker to north direction confirmed by higher magnetic field value between 230.1 to 2541 nT.